A critical review of theoretical aspects of strategic planning and firm performance - Ibraimi, Dr. Sadudin (International Journal of Scientific Research and Management (IJSRM), 2019)
In this paper we examine the reasons and justify the striking interest being taken by researchers and managers on strategic planning, but also the limits of those principles, some intrinsic others that can be overcome by an integration with tradition. A framework which attempts to relate the constituent elements that distinguish the two main strategic theories and shows that both must be considered for strategic planning and performance management is provided